Analysis of Exchange Rate and Welfare of Sutchi Catfish (Pangasius hypophthalmus) Farmer Households In The Minapolitan Area of Banjar Regency, South Kalimantan Province - Hasanul Basri; Idiannor Mahyudin; Leila Ariyani Sofia (International Journal of Science and Environment (IJSE), 2026)
Sutchi catfish products in South Kalimantan are predominantly sold live or fresh for consumption purposes, with marketing areas covering South Kalimantan, Central Kalimantan, and East Kalimantan. Processed sutchi catfish products remain limited and have not yet provided substantial added value to sutchi catfish production; therefore, fish commodity prices are strongly influenced by consumption levels and supply availability. This study aimed to analyze the Fish Farmer Exchange Rate and to categorize the household welfare level of sutchi catfish farmer households in the Minapolitan area of Banjar Regency, South Kalimantan. The study was conducted in six villages, namely Sungai Sipai, Tungkaran, Cindai Alus, Sungai Batang, Panggalaman, and Sungai Rangas Hambuku. Data were analyzed using a quantitative descriptive method, particularly the Fish Farmer Exchange Rate approach for classifying farmer household welfare. The results showed that the welfare level of sutchi catfish farmer households in the Minapolitan area of Banjar Regency was generally in the high category. This was indicated by 77 respondents, or 93.5%, having a Fish Farmer Exchange Rate of >100, meaning that income from sutchi catfish farming was sufficient to cover or exceed household and production expenditures. Meanwhile, only 3 respondents, or 3.9%, were in the low welfare category with a Fish Farmer Exchange Rate of <100, and 2 respondents, or 2.6%, were in the medium welfare category with a Fish Farmer Exchange Rate of =100.